The Analysis of women's leadership communication styles in group communication - Rahman, Annisa; Susilo, Anindita (Penerbit Universiti Kebangsaan Malaysia, 2024)
Women's leadership continues to change in response to the development of various social changes that occur. This research aims to dig deeper into the communication style of women's leadership in a communication group context, focusing on women leaders in the Universitas Mercu Buana student organization for the 2022/2023 academic year. This research refers to Communication Theory by Sasa Djuarsa Sendjaja which states that leadership styles in groups are divided into five categories, authoritarian style, bureaucratic style, diplomatic style, democratic style, and laissez-faire or group-centered style. With a qualitative case study approach, researchers collect data through data collection and analysis such as in-depth interviews, observation, and documentation. This research uses the constructivism paradigm. In this study, researchers interviewed 5 main key informants and 10 additional informants who are administrators of 5 student organizations active at Universitas Mercu Buana. This research applies Miles and Huberman’s qualitative data analysis technique, then source triangulation is used as a data validity checking technique. The results showed a comprehensive picture of how women leaders in student organizations use their communication styles to give orders, communicate, make decisions, motivate, supervise performance, and lead their group members. The findings show variations in women's leadership communication approaches, with some leaders highlighting assertive leadership, while most lean more towards an inclusive and democratic approach. The researcher can conclude that this study provides a deep insight into the role and contribution of women leaders in group communication, particularly in student organizations.